Rachunek kosztów działań jako instrument zarządzania szpitalem - Kludacz, Magdalena (Application Activity - Based Costing to Hospitals, 2005)
The purpose of this paper is to emphasise the important role of costing system in a decision making process in hospitals. The traditional methods that are used to determine product cost, very often produce wrong information. Thus sometimes managers can make mistakes in their decisions. The article presents a new costing system - ABC that could afford appropriate information about costs of the medical services delivered to the patients. It has been developed by R. Caplan and R. Cooper. ABC systems are designed on the premise that products require "activities" and that these activities, in turn, consume "resources". Activity-based costing is an advanced cost calculation technique that allocates resource costs to products based on activity consumption. Every step of proposed ABC system has been presented in the article. Applying ABC could benefit hospitals in several ways. Apart from providing realistic cost information, ABC could help hospitals improve the quality of their medical services and, at the same time, reduce costs.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 227-235